2020
DOI: 10.1093/jpe/rtaa047
|View full text |Cite
|
Sign up to set email alerts
|

Growth, phenology and N-utilization by invasive populations of Gunnera tinctoria

Abstract: Aims Gunnera tinctoria is an unusual N-fixing plant species that has become invasive worldwide, generally in environments with a low evaporative demand, and/or high rainfall. Amongst the many mechanisms that may explain its success as an introduced species, a contrasting phenology could be important but this may depend on an ability to grow and utilise nutrients under sub-optimal conditions. We examined whether G. tinctoria has an advantage in terms of a contrasting phenology and N-fixing cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…The ability of Alnus species to fix nitrogen in soil could have impacts on native plant communities in Ireland that require low nitrogen levels and where the native A. glutinosa doesn't naturally occur but where A. cordata or A. rubra could grow, however, neither species does well in peat soils (Wilson et al, 2018). A similar issue has been found with Gunnera tinctoria in western Ireland (Mantoani et al, 2020). Long term studies on naturalised stands of A. cordata and A. rubra would be useful in determining both their invasiveness and their potential to either enhance or hinder the biodiversity of both semi-natural and human-made habitats.…”
Section: Discussionsupporting
confidence: 54%
“…The ability of Alnus species to fix nitrogen in soil could have impacts on native plant communities in Ireland that require low nitrogen levels and where the native A. glutinosa doesn't naturally occur but where A. cordata or A. rubra could grow, however, neither species does well in peat soils (Wilson et al, 2018). A similar issue has been found with Gunnera tinctoria in western Ireland (Mantoani et al, 2020). Long term studies on naturalised stands of A. cordata and A. rubra would be useful in determining both their invasiveness and their potential to either enhance or hinder the biodiversity of both semi-natural and human-made habitats.…”
Section: Discussionsupporting
confidence: 54%
“…The study area is the same as that reported in Mantoani et al (2020) and Mantoani and Osborne (2021;2022), and located on Dooega Beach, Achill Island (53º51" and 54º01' N; and 9º55' and 10º15' W), Co. Mayo, on the west coast of Ireland. We evaluated the earthworm populations in four treatments: GRASS, uninvaded semi-natural grasslands, GUN, areas invaded by G. tinctoria, and two G. tinctoria removal treatments, MER, where plants were subjected mechanical removal, and HER, herbicide treatment (RoundUp Flex, Monsanto ® -concentration 4 L ha -1 ).…”
Section: Area Of Study and Experimental Designmentioning
confidence: 84%
“…As well as being a significant invader in Ireland, this species has become invasive in other parts of western Europe, the UK, Portugal, and New Zealand (Osborne et al 1991;Gioria and Osborne 2013). Several aspects of these invasions in Ireland have already been documented, including impacts on the soil seed bank (Gioria and Osborne 2009;2010;Gioria et al 2011), the significance of differences in N-utilisation and phenology (Mantoani et al 2020) and effects on soil greenhouse gas emissions (Mantoani and Osborne 2021). Importantly, experimental evidence, supported by biological records (Fennell et al 2014), have allowed us to date the age of the populations investigated at > 50 years, which enables us to document the time over which any changes have occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Data on leaf number, total leaf area, petiole area, and rhizome area were collected before each sampling time for each individual plant. The conversion of linear dimensions, estimated by measuring tape and/or caliper ruler, to the actual foliar area was determined from photographs analysed with Easy Leaf Area ® software [37] following a previous assessment on invasive G. tinctoria populations [35]. We calculated leaf areas using the equation, Area = ((0.7276 × length × breadth) + 19.538; r 2 = 0.981).…”
Section: Plant Parametersmentioning
confidence: 99%
“…The removal of leaves would significantly reduce photosynthesis, whilst direct N 2 O emissions from plants and soils would increase. Although the mechanism(s) associated with the production of N 2 O by plant tissues is not known [32], the ability of G. tinctoria to fix atmospheric N [33][34][35], could also contribute to increased emissions [36]. Finally, we also hypothesized that waterlogging would reduce photosynthesis in intact plants, primarily through stomatal closure as well as resulting in plant-enhanced [32] and/or increased soil N 2 O emissions [19].…”
Section: Introductionmentioning
confidence: 99%